Enhancing Sustainable Stingless Beekeeping Production through Technology Transfer and Human Resource Development in Relationship with Extension Agents Work Performance among Malaysian Beekeepers - Isah, Ibrahim Aliyu; Olagunju, Oluwatoyin; Ismail, Mohd Mansor; Hassan, Salim; Man, Norsida (Sciencedomain International, 2019)
Stingless beekeeping is not only a profitable activity to Malaysian beekeepers but also to Malaysian economy. However, natural honey has faced some difficulties which resulted to low production due to lack of information on improved technology as well as capacity and potential building of stingless beekeeping farmers which depend mostly on information received from the extension agents. Hence, it is the responsibility of the extension agents to give useful information on the available technology and develop the capacity of the farmers to take right decision that will improve their level of production. This study assessed how technology transfer and human resource development skills influences work performance of the extension agents towards sustainable beekeeping production among beekeepers. The study sought to establish the role of relevant technology transfer and human resource development skills in effective performance. The research design was descriptive and quantitative survey of stingless beekeepers on technology transfer and human resource development by the extension agent. Data was obtained from 54 beekeeping farmers and was analyzed using descriptive and inferential statistics. The results revealed that technology skill, technology dissemination skill, technology evaluation skill, Decision making process skill, Leadership development skill and work performance were rated moderate by stingless beekeeping farmers while Social skill was rated high. Significant and positive correlation (P<0.01) existed between all variables and performance. Regression results showed that leadership development skill, Decision making process skill, and social skill are significant (P = .05), while technology skill, technology dissemination skill, technology evaluation skill are not significant. The highest contributing factor is social skill (β=.446). Beekeeping is a profitable project in Malaysia and can be sustained if the extension services and programmes are well carried out by competent extension agents and relevant agricultural government agency.